2011
DOI: 10.1177/0022146511431418
|View full text |Cite
|
Sign up to set email alerts
|

Changing Work, Changing Health: Can Real Work-Time Flexibility Promote Health Behaviors and Well-Being?

Abstract: Workers increasingly report time scarcity as a result of two important trends: All adults in a household now tend to work for pay (meaning no back-up homemaker) and a competitive global economy pushes employers to require fewer workers to do more with less. Nevertheless, rules and expectations about the social organization of work time are outdated, having been designed for a different type of workforce and different types of work in the last century.A corporate headquarters was rolling out a workplace innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 0 publications
7
57
2
Order By: Relevance
“…Desirable features of a tool include a defined assessment protocol, adequate characterization of healthy versus unhealthy foods, assessment of price, availability, quality, and promotion of food (as these might influence consumer behavior), reliability, and validity. To date, most tools have accessed the consumer food environment in supermarkets, grocery stores, or convenience stores (Moen et al, 2011). Still, they have not reached non-traditional food places such as farmers' markets (Schultz et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Desirable features of a tool include a defined assessment protocol, adequate characterization of healthy versus unhealthy foods, assessment of price, availability, quality, and promotion of food (as these might influence consumer behavior), reliability, and validity. To date, most tools have accessed the consumer food environment in supermarkets, grocery stores, or convenience stores (Moen et al, 2011). Still, they have not reached non-traditional food places such as farmers' markets (Schultz et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, they were unable to determine whether these differences were due to individuals in Asian countries having to work for long work hours and face huge work demands or due to the difference in reporting. Some studies from Western countries have demonstrated that organization support and flexible work arrangements are useful in decreasing WFC and enhancing well-being (Kossek et al, 2011;Moen et al, 2011). Such research on WFC in China is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…They stress that reducing the mismatch should increase the motivation and productivity of employees while reducing absenteeism caused by health issues. Moen et al (2011) find that greater schedule control and reduced work-family conflict for employees result in positive changes in their health and in measures of wellbeing. Konrad and Mangel (2000) examine whether companies that have given flexibility to employees to help them balance their demand for work and personal life are more productive.…”
Section: Ijoa 273mentioning
confidence: 87%